Investigating Computer Science Students’ Identification with the Course and Their Perceptions of the Content Taught - Zandoná, Daniel; Kockelke, Finn; Mello, Rafael de (Anais do Workshop sobre Educação em Computação (WEI); 2024: Anais do XXXII Workshop sobre Educação em Computação, 2024)
Brazilian public universities have several high-level and traditional Bachelor courses in Computer Science (BCS), of which quality is largely recognized in society. However, informal talks with students from these courses reveal a recurrent concern with the content taught and their readiness for the industry. In this study, we investigate the relationship between the students’ social identity with their BCS and their perceptions about the content taught. For this purpose, we conducted an opinion survey with students from a traditional BCS course. The study findings reveal that the students tend to feel they belong to their BCS, recognizing its distinctive view in the industry. However, we found that the students with higher identification with the course also tend to be more critical about the content taught.